Strain Assessment in Surgically Resected Inflammatory and Neoplastic Bowel Lesions - Havre, R. F.; Leh, S.; Gilja, O. H.; Ødegaard, S.; Waage, J. E.; Baatrup, G.; Nesje, L. B. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: To investigate whether ultrasound-based strain imaging can discriminate between colorectal adenocarcinomas and stenotic Crohn’s lesions in newly resected surgical specimens.Materials and Methods: Resected surgical specimens from 27 patients electively operated for colorectal tumors or stenotic lesions from Crohn’s disease were prospectively examined with ultrasonography using a Hitachi HV 900 US scanner with real-time elastography (RTE). Three different methods were applied to assess tissue strain: A four-level categorical visual classification, a continuous visual analog scale (VAS, 0 – 100) and a strain ratio (SR) measurement between the lesion and surrounding reference tissue. The imaged sections were marked and subsequently examined by a pathologist. Results from RTE were evaluated according to diagnosis, degree of fibrosis, inflammatory parameters, tumor stage and grade.Results: 16 sections from Crohn’s lesions, 18 sections from adenocarcinomas and 4 sections from adenomas were examined. Both adenocarcinomas and Crohn’s lesions were found to be harder than the surrounding tissue, but they could not be discriminated from each other by any of the strain imaging evaluation methods. All adenocarcinomas had significantly higher strain ratios than adenomas. The categorical classification differentiated poorly between Crohn’s lesions, adenocarcinomas and adenomas. Categorical evaluation and VAS score showed fair interobserver agreement. SR measurements provided semi-quantitative strain data and added improved information about elasticity properties, despite substantial intra-observer variation.Conclusion: Sonoelastography with SR measurements and visual evaluation of strain differences could not differentiate stenotic Crohn’s lesions from adenocarcinomas in resected bowel specimens. A small number of adenomas were found to be significantly softer than adenocarcinomas using the same evaluation methods. The tumor stage or grade did not have a significant impact on the elastography results.
Keywords: ultrasound; adenocarcinoma; Crohn’s disease; strain ratio; ex-vivo